COVID-19 in Latin America and the Caribbean with a Special Focus on Perú, México, and Cuba. Issue 1 (March 2023) - Pineo, Ronn; Shaver, Carrie; Creel, Kelcie; Pritchard, Chelsea
This essay offers a summary of the impact of COVID-19 and efficacy of the responses in Latin America and the Caribbean, with a particular focus on Perú, México, and Cuba. Because so much has already been written on COVID-19, the goal of this article is to move beyond what has already been said, providing a briefing on what has been most unusual and counter-intuitive regarding the pandemic in the region. Focusing on Perú, México, and Cuba allows the spotlighting of several critical issues. Cuba, with a model public health care system and successful bio-tech sector, was largely spared the first wave of the pandemic, only to be severely affected by the Omicron variants. Perú and México have suffered during the pandemic the very worst excess mortality rates in the world. This essay explores these matters, explaining how a lethal confluence of negative forces came together with deadly consequences for the people of Latin America and the Caribbean.